Screening and characterization of mutations in isoniazid-resistant Mycobacterium tuberculosis isolates obtained in Brazil - Cardoso, R. F.; Cooksey, R. C.; Morlock, G. P.; Barco, P.; Cecon, L.; Forestiero, F.; Leite, CQF; Sato, D. N.; Shikama, M. D.; Mamizuka, E. M.; Hirata, RDC; Hirata, M. H. (Amer Soc Microbiology, 2004)
We investigated mutations in the genes katG, inhA (regulatory and structural regions), and kasA and the oxyR-ahpC intergenic region of 97 isoniazid (INH)-resistant and 60 INH-susceptible Mycobacterium tuberculosis isolates obtained in two states in Brazil: São Paulo and Parana. PCR-single-strand conformational polymorphism (PCR-SSCP) was evaluated for screening mutations in regions of prevalence, including codons 315 and 463 of katG, the regulatory region and codons 16 and 94 of inhA, kasA, and the oxyR-ahpC intergenic region. DNA sequencing of PCR amplicons was performed for all isolates with altered PCR-SSCP profiles. Mutations in katG were found in 83 (85.6%) of the 97 INH-resistant isolates, including mutations in codon 315 that occurred in 60 (61.9%) of the INH-resistant isolates and 23 previously unreported katG mutations. Mutations in the inhA promoter region occurred in 25 (25.8%) of the INH-resistant isolates; 6.2% of the isolates had inhA structural gene mutations, and 10.3% had mutations in the oxyR-ahpC intergenic region (one, nucleotide -48, previously unreported). Polymorphisms in the kasA gene occurred in both INH-resistant and INH-susceptible isolates. The most frequent polymorphism encoded a G(269)A substitution. Although KatG(315) substitutions are predominant, novel mutations also appear to be responsible for INH resistance in the two states in Brazil. Since ca. 90.7% of the INH-resistant isolates had mutations identified by SSCP electrophoresis, this method may be a useful genotypic screen for INH resistance.